Obstacles to university food pantry use and student-suggested solutions: A qualitative study. - Aseel El Zein; Melissa J Vilaro; Karla P Shelnutt; Kim Walsh-Childers; Anne E Mathews (PLoS ONE, 2022)
Background In the absence of federal programs and policies to alleviate college student food insecurity, the number of food pantries has grown rapidly in the United States. Yet, no studies, to date, have qualitatively examined students' experiences with this resource. Objective To explore college students' perspectives on barriers to using an on-campus food pantry and provide insights into student-suggested solutions. Methods In this qualitative study, 41 college students were recruited from a large public university in the southeastern US with a campus food pantry. Students participated in one-on-one, in-person, semi-structured interviews. All interviews were audio-recorded, transcribed verbatim, managed using NVivo 12, and analyzed using inductive, semantic thematic analysis. Results Most students were classified as food insecure (n = 33, 82.5%), and two-thirds identified as pantry users (at least once). The students' reasons for not using the food pantry indicated resistance and access barriers. Students either 'chose not to use' the campus food pantry due to (i) stigma and shame, (ii) perceived insufficient need, (iii) and unsuitable food or they experienced 'barriers' due to (i) lack of knowledge and (ii) limited food access. The main reason reported by food insecure non-pantry users was feelings of stigma and shame while that of food insecure pantry users was limited food access. Students suggested three solutions to minimize barriers experienced when utilizing the campus food pantry. These included (i) spreading awareness about the pantry through positive marketing messages that de-stigmatize use, (ii) improving accessibility of fresh produce and protein options, and (iii) improving access through satellite locations and online ordering systems. Conclusion These barriers need to be systematically addressed to normalize food pantry use. Consideration of student recommendations by university program developers and policymakers may be of added value to expand access to food by college students with food insecurity.